Work-related stress and turnover intention during the COVID-19 pandemic among nurses in Hospital Universiti Sains - Siang, Ling Kui (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
The outbreak of the COVID-19 had a significant impact on the healthcare system. This puts the healthcare system under tremendous pressure. Nurses are reported to be under stress following the Covid-19 outbreak, and estimated a mass turnover intention among nurses globally due to the pandemic. Therefore, this study aims to assess the level of work-related stress and turnover intention among nurses in Hospital USM. A total of 365 nurses participated in this study by answering self-administered questionnaire through Google Forms sent to them. The collected data were analyzed by SPSS version 26.0. Sociodemographic characteristics, the prevalence of work-related stress and turnover intention was presented in descriptive statistics. The Pearson correlation test was used to analyze the relationship between work-related stress and turnover intention. To analyze the association between sociodemographic characteristics with work-related stress and turnover intention, the Chi-square test and Fisher exact test were utilized with a significance level of p<0.05. The majority of the nurses experience little to moderate levels of work-related stress; however, they do not have the intention to leave. This study showed a significant and positive correlation between work-related stress and turnover intention. Nevertheless, there were no significant associations between sociodemographic characteristics with work-related stress and turnover intention among nurses in Hospital USM during the COVID-19 pandemic. The findings of the study alert healthcare personnel regarding the issues and consequences related to work-related stress and turnover intention. Therefore, appropriate proactive strategies or recommendations should be done to improve nurses’ satisfaction and address issues related that surround the nursing practice environment to improve the quality of care delivered and patient safety, besides retaining highly skilled nurses.